2007
DOI: 10.1002/ajp.20443
|View full text |Cite
|
Sign up to set email alerts
|

Paracellular nutrient absorption in a gum‐feeding new world primate, the common marmoset Callithrix jacchus

Abstract: The common marmoset is one of the few callitrichid species that is not threatened or endangered in the wild, and is widely used in biomedical research, yet relatively little is understood about its digestive physiology. Dietary specialization on plant exudates has lead to relatively reduced small intestines, yet the common marmoset has exceptional dietary breadth, allowing it to successfully utilize a variety of habitats. We predicted that passive, paracellular nutrient absorption would be used by the common m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
3
12
0
1
Order By: Relevance
“…It has clearly been shown that exudativorous marmosets and strepsirrhines have specific gut adaptations, such as an enlarged, capacious caecum, to promote digestion of exudates (Power, Chap. 2;Nash 1986;Caton et al 1996;Power and Oftedal 1996;McWhorter and Karasov 2007). Studies on the adaptive morphology of the skull and temporomandibular joint, however, have been equivocal (Ravosa et al, Chap.…”
mentioning
confidence: 96%
“…It has clearly been shown that exudativorous marmosets and strepsirrhines have specific gut adaptations, such as an enlarged, capacious caecum, to promote digestion of exudates (Power, Chap. 2;Nash 1986;Caton et al 1996;Power and Oftedal 1996;McWhorter and Karasov 2007). Studies on the adaptive morphology of the skull and temporomandibular joint, however, have been equivocal (Ravosa et al, Chap.…”
mentioning
confidence: 96%
“…However, callitrichines differ markedly in their exudate feeding adaptations and ecology. Tamarins (Saguinus), lion tamarins (Leontopithecus), and callimicos (Callimico) are described as facultative exudate feeders (i.e., they lack the anatomical specializations of the jaws and teeth required for gouging holes in bark), whereas marmosets (Callithrix, Cebuella, Callibella, and Mico) are considered obligate exudate feeders due to their ability to gouge holes into tree trunks and branches to stimulate the flow of exudates, and morphological adaptations associated with efficient digestion of low quality foods in the ceacum and small intestines (Power and Oftedal 1996;McWhorter and Karasov 2007). As a result, for marmosets, exudates are argued to represent stable, renewable, and available resources throughout the entire year (Ferrari and Lopes Ferrari 1989;Rylands and de Faria 1993;Ferrari and Digby 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, exudates contain difficult to digest beta-linked polysaccharides (Anninson et al 1994;Power 1996;Power and Oftedal 1996). In this regard, common marmosets and pygmy marmosets have evolved elongated and complex hindguts (Cebuella also is characterized by long gut transit time relative to body mass) (Coimbra-Filho and Mittermeier 1977;Coimbra-Filho et al 1980;Ferrari et al 1993;Caton et al 1996;Power 1996;McWhorter and Karasov 2007), which serve to increase opportunities for fermentation and more efficient digestion of exudates. Although these feeding adaptations are well documented, little is known concerning the productivity or spatial and temporal availability of exudate sites, or of the behavioral tactics used by foragers to encounter and effectively exploit this resource.…”
Section: Introductionmentioning
confidence: 96%
“…Between samplings, birds were kept in individual cages covered with dark cloth. The standard use of this pharmacokinetic procedure requires sampling from the same individuals for all blood samples and for each individual to receive both gavage and injection treatments (Chang and Karasov, 2004;McWhorter and Karasov, 2007;Tracy et al, 2007). However, because of their small m b , and consequently small blood volume, we were only able to take two blood samples from (N37) and refed (N36) treatments upon initial capture, and during refeeding in the refed treatment.…”
Section: Paracellular Uptake Experimentsmentioning
confidence: 99%